PENGARUH UKURAN PERUSAHAAN DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN MELALUI KINERJA KEUANGAN PADA PERUSAHAAN PROPERTY DAN REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2019-2021 - Kamiliya, Kamiliya; Wiryaningtyas, Dwi Perwitasari; Pramitasari, Triska Dewi (Jurnal Mahasiswa Entrepreneurship (JME), 2023)
A company is an organization with a legal entity that has an important role in the economic development of a country. The aim of this study is to determine the effect of company size and profitability on company value through the financial performance of property and real estate companies that are listed on the Indonesia Stock Exchange in 2019-2021. This current study employed a purposive technique sampling. The data analysis and hypothesis testing in this study used Structural-Partial Least Square Equation Model (PLS-SEM). The results of the direct influence hypothesis test using the Smart application PLS 3.0 shows that company size has no significant effect on financial performance, profitability has a significant effect on financial performance, company size has no effect significant to firm value, profitability has no effect significant to firm values, financial performance has no effect significant to firm value. The results of the indirect hypothesis test show that firm size through financial performance has a negative but not significant effect on the firm values and profitability through performance financial effect positive but not significant to firm value.